POWER RELATIONS IN INCLUSIVE EDUCATION: A REVIEW OF THE SOCIOLOGICAL LITERATURE ON DISCRIMINATORY PRACTICES AGAINST CHILDREN WITH SPECIAL NEEDS: RELASI KUASA DALAM PENDIDIKAN INKLUSIF: KAJIAN LITERATUR SOSIOLOGIS TERHADAP PRAKTIK DISKRIMINATIF TERHADAP ANAK BERKEBUTUHAN KHUSUS - Gembong Rudiansyah Sumedi; Masrur; Muchamad Arifin; Oman Sukmana (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Inclusive education is a global and national mandate that aims to provide equitable access to education for all children, including children with special needs (ABK). However, its implementation is still colored by veiled discriminatory practices. This study aims to examine how power relations in educational institutions shape the experience of ABK in schools, as well as analyze how educational structures can reproduce social injustice. This research uses a qualitative approach with a systematic literature review method based on a critical sociological perspective. The data source is in the form of secondary literature from journal articles, scientific books, research reports, and relevant policies in the period 2017–2025. Data was collected through systematic searches in various scientific databases and analyzed thematically and interpretively. The results of the study show that inclusive education is still fraught with unequal power relations through labeling, normalization, and institutional resistance to diversity. ABK is often marginalized because of non-inclusive normative standards. These findings affirm the importance of transforming the education system through a critical, reflective, and social justice-based approach. This research recommends curriculum reform, transformative teacher training, and structural support that ensures the full participation of children with disabilities in education.